The Effect of Cross-Sectional Shape of Pile Foundation on the Bearing Capacity and Settlement for the Kobema Bengkulu SPAM Filter Building - Ibtisamah, Athiyyah Meisu; Misliniyati, Rena; Amri, Khairul; Fikri, Muharram Nur; Supriani, Fepy (Rekayasa Sipil, 2025)
This study aims to investigate the impact of dimensional variations on the bearing capacity and settlement of filter buildings in the Benteng Kobema Bengkulu Regional Drinking Water Supply System (SPAM), which has a capacity of 380 L/second and plays a crucial role in providing clean water to the community. Given the potential risk of the Mentawai Pagai Megathrust subduction earthquake, it is necessary to evaluate the bearing capacity and settlement of building foundations. Based on the results of the Standard Penetration Test (SPT), the effect of variations on bearing capacity and settlement can be determined using two types of pile cross-sections, namely square and circular, accompanied by differences in pile cross-section dimensions, namely 300 mm, 400 mm, 500 mm, and depths of 7 m, 9 m, 11 m, and 13 m. The comparison is based on the bearing capacity of the foundation and the settlement of the pile foundation for the filter building of the SPAM Kobema Bengkulu project, using several methods: Poulos and Davis, Reese and Wright, Luciano Decourt, and the Finite Element Method. The smallest settlement is obtained by comparing the total settlement with the allowable settlement, which is 10% of the diameter. The test results show that the bearing capacity, deflection magnitude, and smallest settlement are below the permissible settlement limit, which is less than 10% of the foundation dimensions. The comparison between the static and numerical methods, or the Bearing Capacity Ratio (BCR), is closer to 1, indicating a more efficient and safer approach. In this analysis, a BCR value approaching one was obtained for a square-section foundation with a size of 500 mm, using the Reese and Wright method at a depth of 9 m. This yielded a bearing capacity of 312.04 tons for a single pile and 207.69 tons for a group of piles.